On matrix representation of nonlinear maps - Bekbaev, Ural (Federation of Engineering Institutions of Islamic Countries, 2016)
The majority of maps we deal with in different fields of research, particularly in Engineering, are nonlinear maps. For application, calculation, approximation and theoretical purposes the representation of such maps by matrices, around a fixed point, is important. The current paper deals with this problem in general finite dimensional case. The matrix representation of maps is introduced, its basic properties are proved and discussed.